A sequential approach to reduce sodium chloride in freshwater fish burgers considering chemical, texture, and consumer sensory responses - Rios Mera, Juan Dario (2024)
The objective of this work was to determine the effect of the reduction and substitution of salt (NaCl) in pacu (Piaractus brachypomus) burgers, an Amazonian freshwater fish. In the first stage, five treatments with NaCl concentrations from 0.5 to 1.5 g/100 g were evaluated for proximal composition, instrumental texture, cooking losses, sensory profile, overall liking, and lipid oxidation for eight weeks. The results suggest a 50% reduction in NaCl content without affecting the parameters of burgers. In the second stage, NaCl was replaced up to 50% by potassium chloride (KCl) or calcium chloride (CaCl2), observing that CaCl2 at 50% substitution of NaCl presents better compatibility with the product in the chemical aspect, instrumental texture, sensory profile and overall liking, with the improvement in the decrease of the lipid oxidation compared to the product with only NaCl. The NaCl reductions in the two stages reached up to 75% NaCl reduction in the burger, showing the salience of studying first the NaCl reduction and then the incorporation of NaCl substitutes.